2000
DOI: 10.1046/j.1365-246x.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of experimental dynamos

Abstract: Summary Laboratory models of geophysical magnetic field production require new experi‐mental characterization methods. Self‐generating liquid metal magnetic dynamos are explored using two new experiments. Kinematic dynamo studies lead us to charac‐terize the magnetic field dynamics in terms of eigenvalues and eigenfrequencies of the induction equation. Observing the decay of magnetic field pulses indicates the real part of the leading eigenvalue of the induction equation, while a chirp magnetic field diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…We will argue here that the VKS dynamo generated when the impellers are counterrotated at equal rates is a dynamo of the ␣-type. Similar s 2 t 2 geometries are being explored in experiments operated by Lathrop and co-workers [51][52][53] at University of Maryland College Park and by Forest and co-workers [54][55][56] at University of Wisconsin, Madison. Sodium flows are generated in spherical vessels with a diameter ranging from 30 cm to 1 m. Changes in Ohmic decay times using externally pulsed magnetic fields in Maryland have again suggested that the dynamo onset may significantly depend on fine details of the flow generation.…”
Section: B the Vks Experimentsmentioning
confidence: 77%
See 1 more Smart Citation
“…We will argue here that the VKS dynamo generated when the impellers are counterrotated at equal rates is a dynamo of the ␣-type. Similar s 2 t 2 geometries are being explored in experiments operated by Lathrop and co-workers [51][52][53] at University of Maryland College Park and by Forest and co-workers [54][55][56] at University of Wisconsin, Madison. Sodium flows are generated in spherical vessels with a diameter ranging from 30 cm to 1 m. Changes in Ohmic decay times using externally pulsed magnetic fields in Maryland have again suggested that the dynamo onset may significantly depend on fine details of the flow generation.…”
Section: B the Vks Experimentsmentioning
confidence: 77%
“…Sodium flows are generated in spherical vessels with a diameter ranging from 30 cm to 1 m. Changes in Ohmic decay times using externally pulsed magnetic fields in Maryland have again suggested that the dynamo onset may significantly depend on fine details of the flow generation. 52,53 Analysis of induction measurements, i.e., fields generated when an external magnetic field is applied in Madison have shown that turbulent fluctuations can induce an axial dipole and have suggested that a bifurcation to a transverse dipole may proceed via an on-off scenario, 55,57,58 as observed also in the Bullard-von Kármán experiment. 59…”
Section: B the Vks Experimentsmentioning
confidence: 87%
“…Under the guidance of D. Lathrop at the University of Maryland, there have been impressive efforts to build a working dynamo (Peffley, Goumilevski, et al, 2000;Shew et al, 2001).…”
Section: A Marylandmentioning
confidence: 99%
“…We also hope that this work may be of help to the ongoing experiments of spherical Couette dynamo, e.g. the dynamo experiment in Maryland (Peffley et al 2000).…”
Section: Discussionmentioning
confidence: 93%
“…This simple dynamo model captures one of the important ingredients in dynamo action, namely differential rotation. The need to understand dynamo action at realistic values of the magnetic Prandtl number has spawned a number of liquid metal dynamo experiments using differential rotation in a spherical geometry, examples of which are in Grenoble (Cardin and Brito 2007) and Maryland (Peffley et al 2000). These experiments motivate the present study.…”
Section: Introductionmentioning
confidence: 99%